Flood mitigation education for the community of Dul Village, Central Bangka - Maulana Arif; Rasmiati Rasmiati (Universitas Muhammadiyah Magelang, 2022)
Floods are a regular phenomenon in Indonesia, particularly in the Bangka Belitung region. Natural elements such as soil conditions and excessive rainfall, as well as non-natural variables such as rubbish, concretization in infiltration zones, development in floodplain areas, and so on, all contribute to flood disasters. Dul Village, Pangkalanbaru District, Central Bangka Regency, was one of the flood-affected areas. To assist the community in overcoming issues, community service activities will be carried out with the long-term goal of establishing a flood response community, with the specific goal of providing flood disaster mitigation education to the community. A flood disaster socialization program and an early warning system for the community are among the methods employed to carry out this program. The outcomes of this program have increased public awareness of the potential and causes of flooding, particularly in Dul Village, as well as the function of the early warning system in mitigating flood-related losses.